Formulation of Coated Tablets Film of Jengkol Fruit Seeds (Pithecellobium lobatum Benth.) as A Selenium Herbal Supplement - Dolih Gozali; Mutakin Mutakin; Yunita Yunita; Norisca Aliza Putri (Universitas Padjadjaran (Unpad), 2020)
The correlation between the high content of selenium (Se) in plasma and the low prevalence of cardiovascular disease has been published in previous epidemiological studies. The content of Se in the plasma is determined by daily intake. A preliminary surveillance of Se content of several plants showed that the seeds of jengkol (Pithecellobium lobatum Benth.) has the highest concentration of Se. This study aims to develop a pharmaceutical formulation of Se supplement for adjuvant therapy of cardiovascular disease. The jengkol seeds was made into film coated tablets with a wet granulation method. Optimization of the core tablet formula was carried out with variations of binder concentration and coating material. Evaluation was carried out on uniformity of size and weight, disintegration time, hardness and friability. The content evaluation was carried out including the levels of Se, water content, ash, fat, protein, carbohydrate and crude fiber. The results showed that the F3 had the lowest friability and highest hardness. The coating of tablets using PVA has covered the smell of jengkol seed. The evaluation results showed that film coated tablets contained the Se level content of 0.074 ± 0.004 µg/g, water content of 2.19%, ash content of 1.88%, fat content of 0.89%, protein content of 0.66%, carbohydrate content of 94.38% and crude fiber content 1.79%. The results showed that the jengkol seed film coated tablet formulation could be used as a supplement in additional therapy for cardiovascular disease.Keywords : Pithecellobium lobatum, film coated tablet, herbal supplement, selenium